2005
DOI: 10.1097/00044067-200507000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial Pain—Part I

Abstract: Orofacial pain is a common complaint, affecting the lives of millions of people around the world. Chronic orofacial pain often constitutes a challenging diagnostic problem that can be complicated by psychosocial factors and typically requires multidisciplinary treatment approaches. The fundamental prerequisite for successful management of orofacial pain is an accurate diagnosis. Generating a differential diagnosis, which will ultimately lead to a definite diagnosis, requires thorough knowledge of the diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…There is considerable variability in prevalence, cause, and treatment of these disorders. More detailed reviews on neuropathic pains classification, etiology, and pathophysiology can be found elsewhere 12,67,68…”
Section: Neuropathic Painmentioning
confidence: 99%
“…There is considerable variability in prevalence, cause, and treatment of these disorders. More detailed reviews on neuropathic pains classification, etiology, and pathophysiology can be found elsewhere 12,67,68…”
Section: Neuropathic Painmentioning
confidence: 99%
“…Orofacial pain is often complicated by psychological factors and may require multidisciplinary therapy. The medical history and physical examination, laboratory testing, and imaging findings enable selection of the optimal choice of therapy [ 1 2 ]. It has been shown that the sympathetic nervous system is usually involved in various pain disorders such as postherpetic neuralgia, complex regional pain syndrome (CRPS), and orofacial pain [ 3 4 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Animal models of neuropathic pain following peripheral nerve injury result in behavioral signs of thermal hyperalgesia and mechanical allodynia in the affected limbs [e.g., 3, 15, 19]. Most animal models of trigeminal nerve injury involve constriction, ischemic injury or transection of the infraorbital or inferior alveolar nerves [7, 11–13, 24] or the mental nerve [9, 10, 1618, 23].…”
Section: Introductionmentioning
confidence: 99%